MEDIA PEMBELAJARAN SISTEM AUDIO UNTUK PEMBERDAYAAN PENDIDIKAN DI KOMUNITAS MASYARAKAT - Mustika, Rieka (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
This study aims to produce a study using a computer program called by the name of CAI (Computer Assisted Instruction). By using the main software Macromedia Authorware and several other supporting software, can produce products with quality picture and sound good. CAI can help students more motivated to learn in a fun way. This research method is the research development. This study begins with a needs analysis followed by the design, product development, implemented, then the product was evaluated and revised. Development Media Audio is a material that contains both theory and practice. CAI as a learning medium can support the learning process to achieve goals effectively and efficiently. Development Media Audio is a demanding learning materials to produce instructional media such as audio programs. With an audio program produced more interesting because the material presented in the study is still in the form of an analog system. While the material is packaged in the form of learning package CAI has a digital recording system.